2009
DOI: 10.1136/bmj.b2462
|View full text |Cite
|
Sign up to set email alerts
|

Association between mid-life marital status and cognitive function in later life: population based cohort study

Abstract: Objectives To evaluate whether mid-life marital status is related to cognitive function in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
175
8
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(232 citation statements)
references
References 51 publications
26
175
8
12
Order By: Relevance
“…Social class was included as a 6-category variable: professional, managerial, skilled nonmanual, skilled manual, semiskilled manual, and unskilled manual. As Håkansson et al 26 suggested that cohabitation was associated with reduced risk of cognitive impairment and AD in later life, partnership status was included as a binary (married or partnership versus single) covariate in the analyses. Smoking was assessed according to participants' number of cigarettes smoked per day.…”
Section: Covariatesmentioning
confidence: 99%
“…Social class was included as a 6-category variable: professional, managerial, skilled nonmanual, skilled manual, semiskilled manual, and unskilled manual. As Håkansson et al 26 suggested that cohabitation was associated with reduced risk of cognitive impairment and AD in later life, partnership status was included as a binary (married or partnership versus single) covariate in the analyses. Smoking was assessed according to participants' number of cigarettes smoked per day.…”
Section: Covariatesmentioning
confidence: 99%
“…Social Isolation: Those widowed or divorced in midlife and still so at follow-up were at higher risk of showing cognitive impairment compared with persons married or cohabiting. 24 5. Metabolic Syndrome and Adiposity: Metabolic syndrome prospectively predicted risk of developing cognitive impairment in older women 25 ; higher levels of all adiposity measures were prospectively associated with worsening cognitive function in men 26 ; and in midlife, there was an increased risk of dementia for obese persons, but the risk estimates were reversed in assessments of late-life body mass index.…”
Section: Table 2 Key Results About Other Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Эти дополнительные данные представлены в таблице 2 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: церебральная амилоидная ангиопатия сосудистая дисфункция и unclassified
See 1 more Smart Citation
“…Håkansson and associates (27) from Sweden and Finland studied 2000 persons in 1972 to 1987 (midlife visit) and 1449 during a reexamination in 1998, an average of 21 years later (later life visit). Data on several vascular-and lifestyle-related factors were collected at both times.…”
Section: Midlife Marital Status and Later Life Cognitive Functionmentioning
confidence: 99%